“Hate Speech as a Limit on Freedom of Expression”: A Critical Analysis of Irene Spigno’s Work in the Context of Democratic Erosion - Peña Barrios, Angello (Revista Internacional & Comparada de Derechos Humanos, 2026)
The work of Irene Spigno critically examines the tension between freedom of expression and hate speech, highlighting how constitutional models and international law have shaped the limits of this right. It traces the circulation of constitutional ideas, the theoretical foundations of free speech, and broadens the definition of hate speech to include gender and sexual orientation. At the same time, it warns that hate speech legislation—originally designed to protect democracy—can be misused in contexts of democratic erosion to silence legitimate dissent and strengthen authoritarian projects, as documented in cases from Europe, Russia, Rwanda, and Venezuela. Overall, the book provides a solid comparative and normative framework while cautioning against the authoritarian instrumentalization of these laws to undermine pluralism and human rights.